KARAKTERISTIK UNSUR TANAH JARANG (LTJ) LANTANUM DAN CERIUM PADA LAPUKAN GRANIT DI DAERAH PARMONANGAN - Musyaffa, Muhammad Ayyasy; Patonah, Aton; Faisal, Reza Mochammad (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2024)
As a critical mineral category, the demand for rare earth metals (LTJ) has increased significantly. Rare earth metals, Lanthanum (La) and Cerium (Ce), are utilized in a variety of contemporary technologies. Rare earth elements such as La and Ce are present in rare earth element-bearing minerals and can be found in granitoid-weathered deposits. The purpose of this study is to determine the characteristics of La and Ce elements conttained in ion adsorption deposits resulting from the weathering of granite boulders, as well as their relationship to other chemical elements. In this study, acid igneous rock weathering samples obtained from drilling in Parmonangan District, North Tapanuli Regency, North Sumatra were analyzed to identify La and Ce element-bearing minerals, enrichment zones, and types of rare earth element deposits. La is enriched in the rare earth element accumulation zone of the ion adsorption precipitate model, while Ce is enriched in the leaching zone, according to the findings of the investigation. This occurs as a result of the movement of La element during weathering, which is then bound by alteration minerals such as kaolinite. As a result of the oxidation process in the rare earth element leaching zone, the element Ce has a distinct ion value, resulting in limited mobility.